Librarians Collaborating with Teaching Faculty: Successful Ways - Wijayasundara, N.D. (South Eastern University of Sri Lanka, Oluvil, 2015)
Ways of accessing information is changing due to ever increasing volume of information and to the rapid development of technology. Librarians need to find out solutions to handle this scenario. One successful method is to work collaboratively with teaching faculty. Survey research method was applied in this study. Though there are different ways to librarians to collaborate with teaching staff in Sri Lankan universities, a systematic study has not been carried out locally to find out different ways based on their perception. A randomly selected sample of 36 teaching faculty and librarians from 3 universities; Peradeniya, Moratuwa and Ruhuna were tested in this study. Interview script consisting of 14 questions was the main data collection instrument. Qualitative data analysis was carried out using software package SPSS Text Analysis for Surveys TM 2.0. Managing and refining 81 elements of raw data ended up with 11 meaningful categories. These categories were the identified ways of collaborating librarians with teaching faculty in this study. Information literacy instruction, team teaching, curriculum reviewing, designing assignments, co-supervision of research projects, collection development, and collaborative research are some of the themes that extracted under faculty library collaboration. Information literacy programmes scored the highest value (89%) whereas the curriculum development method scored the lowest value of 17%. Further this study will facilitate authorities to identify the expectations of collaborators and to address the issues concerned by them ensuring effective faculty-library collaboration in universities.
Keywords: Faculty-library Collaboration; Teaching Faculty; Librarians; Library Services